Respuesta :
Answer:
[tex](c^{2}+d)+2(cd)[/tex]
Step-by-step explanation:
we know that
The algebraic expression of the phrase " The sum of square of c and d" is equal to adds the square of number c to the number d
[tex](c^{2}+d)[/tex]
The algebraic expression of the phrase " The sum of square of c and d increased by twice their product" is equal to
[tex](c^{2}+d)+2(cd)[/tex]
Answer:
c^2+d^2+2cd
Step-by-step explanation:
Sum= addition
square of c= c^2
square of d= d^2
increased= addition
product= multiplication
twice= 2*
Hope this helps :)